Realitas Magis pada Musik Tradisi Minangkabau: Sebuah Perspektif Kajian Budaya - Wardizal Wardizal (Journal of Music Science, Technology, and Industry, 2022)
Purpose: This paper aims to briefly discuss the magical aspects of traditional Minangkabau music. Magical reality is found in some traditional music such as the use of spells, the process of making musical instruments, how to treat musical instruments and the use of facilities in musical performances. This article aims to understand the form and function of magical practice in the context of Minangkabau traditional music. Research Methods: This phenomenon is discussed through the perspective of cultural studies as a form of dialectic between adat (art processes) and the religion of the Minangkabau community. Results and Discussion: The Minangkabau community is a devout Muslim. They only believe in God as taught by Islam. Thus, all the actions of the Minangkabau people must be based on the rules justified by Islam. Although in Islamic belief, shamanism, magic or all forms of activity or behavior are “sirik”, shamanic practices or magical ritual activities are still practiced in the community. Implication: Beliefs and behaviors related to magic are essentially part of Minangkabau culture which contains ideas and feelings, actions and works produced by the community through the learning process.